Ekoteologi dan Gerakan Penghijauan Upaya Membangun Kesadaran Lingkungan Berbasis Spiritualitas Santri Pondok Pesantren As'adiyah Mattirowalie Kab. Bone - Muhsyanur; Satriani, Satriani; Hamzah, Ekawati; Santalia, Indo; Bahri, Syamsul; Umrati, Umrati; Mansur, Mansur; Nurdin, Nurdin; Syafaruddin, Baso (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2025)
This article examines the implementation of the concept of ecotheology in the reforestation movement at the As'adiyah Mattirowalie Islamic Boarding School, Bone Regency as an effort to build environmental awareness based on Islamic spirituality. The environmental degradation that is happening today requires a holistic approach that focuses not only on the technical aspects, but also on the spiritual and moral aspects. Through a qualitative approach with the participatory action research method, this study involved 150 students and 25 ustadz in a reforestation program that integrates Islamic values with environmental conservation practices. The results of the study showed that the ecotheology approach was able to increase the environmental awareness of students by 78% and succeeded in greening an area of 5 hectares around the Islamic boarding school. This program has succeeded in changing the paradigm of students from an anthropocentric understanding to a more sustainable ecocentric view. The implementation of ecotheology in Islamic boarding schools has proven to be effective in creating a generation of Muslims who have a high awareness of environmental sustainability.